Evaluation of Histological Changes in the Salivary Glands of Sprague-Dawley rats Following Injections of Various Forms of Areca Nut Preparations - Kamath, Dr V V (Asian Journal of Pharmaceutics (AJP), 2016)
Introduction: The habit of areca nut chewing impinges on the daily lives of about one-tenth of the world’s population. Areca nut is used in many forms ranging from raw to commercial varieties. The consumption of areca nut is found to have important effects on salivary glands leading to an altered salivary flow rate and pH of saliva. Areca nut consumption is significantly associated with the development of oral submucous fibrosis (OSF). OSF in the early stages is characterized by an increased salivation and advanced stages by an increased dryness of the oral mucosa. Aims and Objectives: The present study aimed to evaluate the histopathological tissue changes in the rat submandibular salivary glands subjected to various forms of areca nut (raw, roasted, and boiled), pan masala extracts, and pure arecoline solution over a period of 36-week. Materials and Methods: 3-4 months old Sprague-Dawley rats were randomly selected and divided into six groups - Control, raw areca nut, boiled areca nut, roasted areca nut, pan masala, and pure arecoline groups; treated with the respective solutions. The control group was treated with distilled water. Rats were sacrificed randomly at an interval of every 6 weeks and submandibular glands dissected out and assessed for any histological changes. Results: Significant histological changes were observed in the rat submandibular tissues including fusion and dilatation of acini and ducts with pooling of the salivary secretions in the initial weeks of treatment and degenerative changes in the later weeks. Among all the groups, the pure arecoline treated group showed significant and early degenerative changes in comparison to the other groups. Conclusion:Chronic consumption of areca nut in various forms leads to deleterious effects on the salivary gland histology leading to degeneration of acini and ductal structures. This degenerative effect leads to an overall decreased salivary output reflecting as dryness of mucosa in the advanced stages of OSF and probably to a decreased local immunity and hence an increased propensity for malignant transformation in the later stages of OSF.